The big book of dashboards visualizing your data using real-world business scenarios - Wexler, Steve 1958-; Cotgreave, Andy 1972-; Shaffer, Jeffrey 1972- (John Wiley & Sons Ltd., 2017)
"The definitive reference book with real-world solutions you won't find anywhere else